High society from a global perspective : mass media and social transformation in the twentieth century - Hornung, Juliane 1989- Herausgeber Verfasser einer Einleitung Verfasser; Hannig, Nicolai, 1980- 25.08.1980- Herausgeber Verfasser einer Einleitung Verfasser; Steinbacher, Emanuel V., 1989- 1989- Herausgeber Verfasser einer Einleitung Verfasser; Szöllösi-Janze, Margit 1957- Herausgeber Verfasser einer Einleitung (Historical social research, 2024)
"This HSR Special Issue seeks to capture the relationship between the mass media and social mobility in the 20th century from a global perspective by introducing the concept of "high society." We argue that in the period around 1900, high society emerged as a rather dynamic and fluid social group that was not only based on birth, wealth, or profession but on media visibility. Since the 1880s, a distinct form of society reporting had been taking shape in the United States, Europe, Asia, and, to some extent, Africa that brought a seemingly private cosmos of love affairs, scandals, and consumerism into view and determined who the new social trendsetters would be. Moving beyond "class," "elite," or "celebrity," this special issue explores how social status in the 20th century was linked to specific media constellations (press, film, radio, television) and constantly changing performance skills. Our authors thus look at different political regimes and economic systems to investigate whether high society developed as a coherent global phenomenon throughout the 20th century or whether we can identify different high societies, bound to specific national media cultures and forms of social stratification. Ultimately, the special issue traces the very media logics of self-promotion and attention management that we associate with todays social media, but which in fact existed long before the launch of the internet."